How families took control of change: Jamie Oliver’s school dinners - Greenfield, Anthony (Henry Stewart Talks, 2017)
The case study describes how Jamie Oliver, a celebrity chef in the UK, tries to improve the health and performance of school children by providing healthy lunches, in the face of opposition from the children… and their parents.